Thermodynamic and dynamic dielectric properties of one-dimensional hydrogen bonded ferroelectric of PbHPO₄-type - Zachek, I.R.; Levitskii, R.R.; Shchur, Ya.; Bilenka, O.B. (Condensed Matter Physics, 2014)
Within the modified model of proton ordering of one-dimensional ferroelectric having hydrogen bonds of PbHPO₄-type, their thermodynamic and dynamic characteristics are studied and calculated taking into account the linear (by crystal deformations ϵi (i=1,3) and ϵ₄) contributions into the energy of a proton system but without taking into account the tunneling in the two-particle cluster approximation. There has been obtained a good quantitative description of the temperature dependence of polarization, static dielectric permittivity, heat capacity and frequency dependence of dynamic dielectric permittivity at different temperatures for PbHPO₄ and PbHDO₄ crystals. У рамках модифiкованої моделi протонного впорядкування з врахуванням взаємодiї протонiв з нормальними коливаннями гратки одновимiрних сегнетоелектрикiв з водневими зв’язками типу PbHPO₄ з врахуванням лiнiйних за деформацiями кристалу εi i ε₄ внескiв в енергiю протонної системи, але без врахування тунелювання в наближеннi двочастинкового кластера розраховано i дослiджено їх термодинамiчнi i динамiчнi характеристики. Отримано добрий кiлькiсний опис температурної залежностi поляризацiї, статичної дiелектричної проникностi кристалiв PbHPO₄ та PbHDO₄, теплоємностi i частотної залежностi динамiчної дiелектричної проникностi при рiзних температурах кристалу PbHPO₄.